The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/jb.00082-08
|View full text |Cite
|
Sign up to set email alerts
|

Specific Partial Reduction of Geranylgeranyl Diphosphate by an Enzyme from the Thermoacidophilic Archaeon Sulfolobus acidocaldarius Yields a Reactive Prenyl Donor, Not a Dead-End Product

Abstract: Geranylgeranyl reductase from Sulfolobus acidocaldarius was shown to catalyze the reduction of geranylgeranyl groups in the precursors of archaeal membrane lipids, generally reducing all four double bonds. However, when geranylgeranyl diphosphate was subjected to the reductase reaction, only three of the four double bonds were reduced. Mass spectrometry and acid hydrolysis indicated that the allylic double bond was preserved in the partially reduced product derived from geranylgeranyl diphosphate. Thus, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(82 citation statements)
references
References 26 publications
2
75
1
Order By: Relevance
“…It was intriguing that the reductase was highly specific to the x-double bond of a geranylgeranyl group. This site-specific reduction was unprecedented and different from the reduction patterns of known archaeal GGRs that typically reduce a geranylgeranyl group to a phytanyl group [14][15][16][17] and of plant-type GGRs that convert it into a phytyl group [18]. The mechanisms responsible for these distinct patterns will be discussed later.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It was intriguing that the reductase was highly specific to the x-double bond of a geranylgeranyl group. This site-specific reduction was unprecedented and different from the reduction patterns of known archaeal GGRs that typically reduce a geranylgeranyl group to a phytanyl group [14][15][16][17] and of plant-type GGRs that convert it into a phytyl group [18]. The mechanisms responsible for these distinct patterns will be discussed later.…”
Section: Discussionmentioning
confidence: 96%
“…4B). Based on the previous data of similar radio-TLC analyses of the GGR reaction products from GGPP and GGGP [16], the slight distance between the spots of the substrate and the product suggested that only one double bond of the geranylgeranyl chain was saturated. This observation was consistent with the fact that tetrahydro-DGGGP-glycerol produced in E. coli cells harboring pBAD-ALB4-MA1492 had one saturated isoprene unit per isoprenoid hydrocarbon chain (Fig.…”
Section: In Vitro Characterization Of Recombinant Ma1492mentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first report of the identification of a physiological electron donor for archaeal GGR. On the other hand, previously isolated GGR from a thermoacidophilic archaeon Sulfolobus acidocaldarius (6) catalyzed the partial reduction of archaeal lipid precursors in E. coli without help from archael ferredoxins, suggesting its relatively broad preference toward electron donors. The effect of the archaeal lipid production on the growth of the host bacterial cells was evaluated because they were supposed to possess an unnatural archaeal-bacterial chimeric lipid membrane.…”
mentioning
confidence: 99%